The sacred hill of Santa Tecla: cultural heritage and religious tourism on the atlantic coast of Galicia - Ceruti, María Constanza (2024)
Santa Tecla, a Galician mountain with a sacredness that dates back to Celtic antiquity and remains valid to this day through religious tourism, is the subject of this significant research. This study aimed to analyse and interpret the importance of this sacred hill in the context of the coastal cultural landscape in the extreme south of Galicia. The methodology is based on participant observation during an ascent on foot to the summit from the town of La Guarda, visiting the Galician-Roman fort of Santa Trega, the archaeological museum of the same name, the viewpoints on Pico San Francisco and the hermitage dedicated to the Saint; as well as in the collection of spontaneous testimonies from visitors, pilgrims and locals; an informal interview with the person in charge of the sanctuary and the photographic record of votive offerings, religious images and souvenirs. The observations reveal the hill as a palimpsest of materialities of symbolic importance, from the Chalcolithic rock art associated with the pre-Roman fort to a possible place of Galician-Roman worship dedicated to fertility. The pilgrimage and contemporary tourism in Santa Tecla bring local and foreign visitors closer to a direct experience of the symbolic dimension of the Atlantic mountain in Galicia.